Correction to: Four‑Dimensional (4D) Bioprinting: A Systematic Scoping Review of Stimuli‑Responsive Constructs for Applications in Tissue Engineering and Drug Delivery - Moghaddas, Mohammad; Oktay, Büşra; Bingöl, Ayşe Betül; Yanıkoğlu, Reyhan; Çiftçi, Fatih; Üstündağ, Cem Bülent (Springer, 2025)
The publication of this article unfortunately contained mistakes. There were several errors within the text. The corrected text is given below. Citation–claim mismatch errors In this section, we categorize errors where manuscript claims are inconsistent with the cited literature and specify the requested changes.